2009
DOI: 10.3325/cmj.2009.50.151
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Intoxication in Pediatric Age: Ten-year Retrospective Study

Abstract: Methods Data on children hospitalized due to intoxication were retrieved from hospital medical records. Children were classified into 4 age groups: 0-5, 6-9, 10-13, and 14-18 years, and their sex and type of intoxication were recorded. For children with alcohol intoxication, data on time of intoxication, reason for drinking, presence of injuries or suspected suicide attempts, and possible presence of other drugs in the organism were collected.Results Out of 29 506 hospitalized children, 594 were hospitalized d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
33
1
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 7 publications
7
33
1
3
Order By: Relevance
“…1 Çocukluk çağında alkol zehirlenmelerinin epidemiyolojisini gösteren ça-lışma sayısı da azdır. 2,[11][12][13] Genellikle alkol ve neden olduğu psikososyal sorunlar üzerine yapılan çalış-malar literatürde bulunmaktadır. Bizim çalışma-mızda acil servisimize başvuran 1871 zehirlenme olgusunun %2,3'ünü alkol zehirlenmeleri oluştur-maktaydı.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…1 Çocukluk çağında alkol zehirlenmelerinin epidemiyolojisini gösteren ça-lışma sayısı da azdır. 2,[11][12][13] Genellikle alkol ve neden olduğu psikososyal sorunlar üzerine yapılan çalış-malar literatürde bulunmaktadır. Bizim çalışma-mızda acil servisimize başvuran 1871 zehirlenme olgusunun %2,3'ünü alkol zehirlenmeleri oluştur-maktaydı.…”
Section: Discussionunclassified
“…Acil servise başvuru anında olguların GKS ortanca değeri 15 (7)(8)(9)(10)(11)(12)(13)(14)(15), ZŞS ortanca değeri 1 (0-3) idi. Sadece 3 (%7,0) olgunun GKS≤8 idi.…”
Section: Bulgularunclassified
“…Our study showed the mean age of alcohol poisoned patients (mean ± standard deviation) 14.91 ± 1.45 years. Croatian study by Bitunjac and Saraga [15] found that 73.2% of children were hospitalized on weekends and 79% of children got intoxicated outdide their homes.…”
Section: Discussionmentioning
confidence: 99%
“…Analyses of sex differences revealed no statistically significant differences between male and female participants ( 1 Due to small case numbers the last two response categories in all three AUDIT items were collapsed. 2 Refers to participants who reported regular alcohol use. 3 According to DSM-IV.…”
Section: Prevalence Of Substance Use and Use-related Problemsmentioning
confidence: 99%
“…In many European, countries the number of adolescents admitted to in-patient treatment with alcohol intoxication (AIA) has dramatically risen over the last 10 years [1][2][3]. In Germany, this figure increased for individuals between the ages of 10 and 20, from 14,105 cases in 2003 to 26,673 in 2012 [4].…”
Section: Introductionmentioning
confidence: 99%